Biology and management of mimosa invisa mart. in Kerala - Jayasree P K (Department of Agronomy, College of Horticulture, 2005)
Mimosa invisa Mart. ex. Colla, called giant sensitive plant (Anathottavodi or Padayincha in Malayalam), a native of Tropical America, introduced in Kerala in 1964, is now a problem to both cultivated and wastelands. Being a comparatively new introduction, no systematic and comprehensive work has been undertaken to study the problems associated with the weed and strategies to manage it. Hence, the project entitled “Biology and management of Mimosa invisa Mart in Kerala” was taken up at the College of Horticulture, Vellanikkara during 2001-2004 with the intention to study the distribution and severity of infestation and biology of the plant, the efficiency of different control methods, utility of the plant and its harmful effects.